-10(-9h+8)=550

Divide each term in -10(-9h+8)=550 by -10.

-10(-9h+8)-10=550-10

Cancel the common factor of -10.

Cancel the common factor.

-10(-9h+8)-10=550-10

Divide -9h+8 by 1.

-9h+8=550-10

-9h+8=550-10

Divide 550 by -10.

-9h+8=-55

-9h+8=-55

Subtract 8 from both sides of the equation.

-9h=-55-8

Subtract 8 from -55.

-9h=-63

-9h=-63

Divide each term in -9h=-63 by -9.

-9h-9=-63-9

Cancel the common factor of -9.

Cancel the common factor.

-9h-9=-63-9

Divide h by 1.

h=-63-9

h=-63-9

Divide -63 by -9.

h=7

h=7

Solve for h -10(-9h+8)=550